Batch sodium borohydride hydrolysis systems: Effect of sudden valve opening on hydrogen generation rate - M. J. F. Ferreira (2012)
A study was undertaken in order to investigate the potential of hydrogen (H 2) generation by hydrolysis of sodium borohydride solution (10 wt% NaBH 4 and 7 wt% NaOH), in batch reactors, operating at moderate pressures (up to ∼1.2 MPa), in the presence of a powdered nickel-ruthenium based catalyst, reused between 311 and 316 times, to feed on-demand a proton exchange membrane fuel cell. A different approach to the testing of the performance of the batch NaBH 4 hydrolysis system is explored, by the quick opening of the reactor release gas valve, to satisfy a sudden H 2 demand; and hydrogen generation rates (HGR) are evaluated by changing catalyst amount, operating pressure and successive refueling. The results have shown the tendency of the studied system to maintain constant the H 2 generation rates, before and after one swift interruption, for single fuel injections (for 2.1 wt% of reused Ni-Ru based catalyst, a maximum value of HGR of 0.61 L(H 2)min -1 g -1(catalyst) at 0.4 MPa, or based on the active metal ruthenium, of 47.5 L(H 2)min -1 g -1(Ru), was achieved). This trend was different in the experiments with successive refueling. The present paper go forward in testing the potential of NaBH 4 system over reused Ni-Ru catalyst after supplying a sudden demand of H 2. Bearing in mind the market of low-power H 2-PEMFCs for portable devices, the herein results are original and useful from an application point of view. (c) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.